INTERPRETIVE PERSPECTIVES ON HOW TO DEAL WITH STRESS AND ANXIETY IN MODERN LIFE - Puja Miranda; Hasan Zaini; Irman Irman (Al-Hijr: Journal of Adulearn World, 2026)
Stress and anxiety are becoming significant problems in modern life, especially among individuals exposed to social and work pressures. This research aims to explore the perspective of interpretation regarding the ways taught in the Qur'an and Hadith to overcome stress and anxiety. The purpose of this research is to explore and identify spiritual solutions that can be applied in the context of daily life, especially in facing the challenges of modern times. The method used in this study is a literature review with a tafsir approach, which examines verses of the Qur'an and hadith related to peace of mind and emotion management. This study found that the Qur'an and Hadith provide very relevant guidelines, such as the importance of tawakkul (surrender) to Allah, maintaining a balance in life, and the practice of dhikr and prayer as a way to relieve stress and anxiety. In conclusion, the interpretive perspective offers a profound spiritual approach to addressing stress and anxiety in modern life, which can be implemented as part of mental health prevention and management efforts in society.